2012
DOI: 10.1186/1479-5868-9-69
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of motivational interviewing in health promotion: a Bayesian mediation analysis

Abstract: BackgroundCounselor behaviors that mediate the efficacy of motivational interviewing (MI) are not well understood, especially when applied to health behavior promotion. We hypothesized that client change talk mediates the relationship between counselor variables and subsequent client behavior change.MethodsPurposeful sampling identified individuals from a prospective randomized worksite trial using an MI intervention to promote firefighters’ healthy diet and regular exercise that increased dietary intake of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…Current research in the field of substance abuse supports this causal model and also suggests that therapist use of MI-inconsistent behaviours (e.g., confrontation) impede the expression of change talk and relate to worse treatment outcome (Miller & Rose, 2009). While therapist behaviours and patient change talk have been examined in areas such as gambling (Hodgins et al, 2009) and diet and exercise (Pirlott et al, 2012), determining the relevance of these mechanisms in the treatment of varied mental health problems is an avenue for future research that may be fruitful. In order to examine therapist and patient in-session behaviour, consistent use of MI fidelity measures is necessary.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research in the field of substance abuse supports this causal model and also suggests that therapist use of MI-inconsistent behaviours (e.g., confrontation) impede the expression of change talk and relate to worse treatment outcome (Miller & Rose, 2009). While therapist behaviours and patient change talk have been examined in areas such as gambling (Hodgins et al, 2009) and diet and exercise (Pirlott et al, 2012), determining the relevance of these mechanisms in the treatment of varied mental health problems is an avenue for future research that may be fruitful. In order to examine therapist and patient in-session behaviour, consistent use of MI fidelity measures is necessary.…”
Section: Future Directionsmentioning
confidence: 99%
“…Given that the focus of MI may differ across populations it is possible that the mechanisms of change in MI for substance use disorders may not apply when MI is used for other disorders. There is some evidence that factors such as change talk and MI consistent behaviours are related to treatment outcome in problem gamblers and patients wishing to improve their diet and physical activity (Hodgins, Ching, & McEwen, 2009;Pirlott, Kisbu-Sakarya, Defrancesco, Elliot, & Mackinnon, 2012), however the relevance of MI change mechanisms to the treatment of psychopathological disorders such as anxiety and eating disorders remains to be examined. Given that MI is related to improved treatment outcomes in these diverse mental health populations , uncovering the mechanisms that contribute to the success of MI treatment may help to tailor MI to specific patient concerns and potentially increase positive therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The PHLAME study tested meditational models and assessed the factors involved in the intervention Kuehl, Mabry, Elliot, Kuehl, & Favorite, 2013;Pirlott, Kisbu-Sakarya, Defrancesco, Elliot, & Mackinnon, 2012;Ranby et al, 2011). Process analyses were conducted for the Wellworks-2 (Hunt et al, 2005) and Healthy Directions (Hunt et al, 2007) interventions.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Pirlot et al proved the effectiveness of MI in healthy lifestyle promotion (diet modification and chiefly regular exercise) inves-Motivational interviewing in obesity reduction tigating a group of 202 firefighters in the PHLAME program (Promoting Healthy Lifestyles: Alternative Models' Effects) [35]. Similarly, Hillsdon et al and Hardcastle et al demonstrated that MI is successful in interventions aimed at physical activity increase [36,37].…”
Section: Motivational Interviewing Application In Obesity Reduction -mentioning
confidence: 99%